IMPROVING THE TEACHING OF INTEGRAL CALCULUS USING THE MAPLE COMPUTER MATHEMATICS SYSTEM - Nazarova, К.Ж.; Yerkisheva, Ж.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article discusses the features of using the Maple program for studying integral calculus. For students pursuing higher education in the field of science education, it is very important to have a high level of mathematical knowledge. However, the level of mathematical preparation among students entering educational programs in this field is not always sufficient. One effective strategy to bridge this gap is to improve teaching methods in mathematics education. This study presents a new methodology for teaching integral calculus using the Maple computer mathematics system, aimed at expanding students’ mathematical knowledge and improving their understanding of problem-solving techniques among second-year students of the educational program 6B05449 – Mathematics. The effectiveness of integrating the Maple computer mathematics system into practical calculus lessons has been confirmed by the results of the study.